The Representation of Women in STEM in Québec Science's Space Column: An Analysis of Discourse and Inclusive Writing - Blakeney, Jessica (Université d'Ottawa | University of Ottawa, 2024)
Women in science, technology, engineering, and mathematics (STEM) fields are greatly underrepresented in the Canadian space sector. To better understand their presence in Francophone media from Quebec, this thesis examines the representation of women in STEM in the Space column of the Québec Science magazine, as well as how inclusive writing can improve their representation. It considers that STEM identity is strategic and positional, such that discourse can either perpetuate or dismantle hegemony in these fields. The critical paradigm governs a quantitative content analysis and a critical discourse analysis of discourses used to describe female expertise in this column, both before and after the implementation of inclusive writing. Results reveal that symbolically annihilating discourses are lessened in the second corpus with greater inclusion and with gender-neutral writing. It addresses potential impacts on STEM identity and recommends discursive practices in written media that can improve the representation of women in these fields.
Keywords: women in STEM; inclusive writing; critical discourse analysis; critical theory; feminization